THREATS TO BUSINESS ACCOUNTING DATA IN THE DIGITAL AGE - NEAGU (ION) ANA-REBECA; GORE BEATRICE-ELENA; ION LAURENȚIU-EDUARD; RADU FLORIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This paper we have examined the vulnerability of accounting data to cyber attacks and the limits of protection afforded to it to counterbalance the benefits of the digital era (Bellanova, 2017), so that we can conclude whether digitization brings sufficient benefits to cover the inherent shortcomings. The solutions proposed to businesses by professionals in the field regarding the potetization of accounting data are vast (Gutwirth et al., 2010) and can sometimes mislead the decision maker, i.e. lead to the wrong decision on the most efficient and adapted solution to the business needs. This paper examines the risks experienced by businesses, at the economic level, as a result of increasingly prevalent fraudulent behaviours originating from both the internal and external environment of the company, fostered by the digitalization of the accounting profession and the accounting professional's reaction to these challenges. According to Weinberger (2011), Big Data is an indicator of the changes undergone by businesses in the market, changes due to the impact of information in digital format, which is too numerous to master and control (Aradau et al., 2015).